2020
DOI: 10.1007/s00217-020-03640-7
|View full text |Cite
|
Sign up to set email alerts
|

High pressure and thermal processing on the quality of zucchini slices

Abstract: In response to the market demand for low processed vegetables, high-pressure treatments (400,600 MPa; 1,5 min) were applied on zucchini slices and compared to a traditional blanching treatment. Histological observations, texture and color analysis, pectinmethylesterase (PME) and antioxidant (DPPH) activities were measured and compared to untreated samples. The histological observations revealed that the longer high-pressure treatments (5 min) led to more extended cell lysis and dehydration than the shorter one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…In HPP200, few changes were observed ( Figure 1 B), mainly related to the decrease in cell turgor (dehydration-d) and some cells showed signs of cell detachment (cd). Several authors reported an increase in cell wall thickness (cwt)-swelling, cell damage (cd), and dehydration (d) after pressure treatments on different fruits and vegetables [ 14 , 21 , 26 , 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In HPP200, few changes were observed ( Figure 1 B), mainly related to the decrease in cell turgor (dehydration-d) and some cells showed signs of cell detachment (cd). Several authors reported an increase in cell wall thickness (cwt)-swelling, cell damage (cd), and dehydration (d) after pressure treatments on different fruits and vegetables [ 14 , 21 , 26 , 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…After the treatment with a pressure of HPP500 ( Figure 1 E), the parenchyma cells showed plasmolysis, gaps, and increased cell wall thickness (cwt). Several authors [ 14 , 37 , 38 , 39 ] hypothesized that cells separation was due to the breakage of chemical bonds between the pectic components of the middle lamellae of adjacent cells and/or to the hydrolysis of some other components of the cell wall such as pectin, hemicelluloses, and cellulose.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the stimulation and accumulation of nutraceutical compounds were also observed. The effects of HHP application have been reported for different minimally processed horticultural commodities [ 31 , 32 , 34 , 37 ], whole produce [ 30 , 35 , 36 , 46 ], and juice [ 54 ], demonstrating great efficiency in improving food safety aspects and in maintaining quality.…”
Section: Postharvest Strategies To Extend the Shelf-life Of Fruit And...mentioning
confidence: 99%
“…The parameters were quantified using the application software provided (Texture Exponent for Windows, version 6.1 10.0). Ten samples of each treatment at each time of sampling were analyzed [27].…”
Section: Leaves Texture Determinationmentioning
confidence: 99%